2013
DOI: 10.1016/j.smim.2013.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrates and T cells: A sweet twosome

Abstract: Carbohydrates as T cell-activating antigens have been generating significant interest. For many years, carbohydrates were thought of as T-independent antigens, however, more recent research had demonstrated that mono- or oligosaccharides glycosidically-linked to peptides can be recognized by T cells. T cell recognition of these glycopeptides depends on the structure of both peptide and glycan portions of the antigen. Subsequently, it was discovered that natural killer T cells recognized glycolipids when presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
58
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 72 publications
1
58
1
Order By: Relevance
“…This in turn stimulates carbohydrate specific T-cells (Tcarbs) and leads to the production of high-affinity carbohydrate specific IgGs. 39 , 41 , 42 Considering the mechanism of action in producing conjugate vaccines will help produce knowledge-based vaccines that are target specific, structurally better-defined, both immunogenic and protective, and produced at a much lower cost. 40 This will allow for use on a more global scale to help control pneumococcal infections.…”
Section: Discussionmentioning
confidence: 99%
“…This in turn stimulates carbohydrate specific T-cells (Tcarbs) and leads to the production of high-affinity carbohydrate specific IgGs. 39 , 41 , 42 Considering the mechanism of action in producing conjugate vaccines will help produce knowledge-based vaccines that are target specific, structurally better-defined, both immunogenic and protective, and produced at a much lower cost. 40 This will allow for use on a more global scale to help control pneumococcal infections.…”
Section: Discussionmentioning
confidence: 99%
“…If the glycan is small enough, just one or two sugars as is the case for CSP and TRAP, these glycopeptides can be displayed by the MHC II for recognition by the T-cell receptor. Contrary to classical dogma, Kasper and coworkers have shown that glycopeptides are indeed true T-cell epitopes that can drive CD4 + T-cell help to B cells for the production of antibodies to the glycosylated antigen [4]. Furthermore, antibodies raised against a glycosylated vaccine should be better able to recognize native sporozoites, particularly if the glycosylated antigen represents an important T-cell epitope.…”
mentioning
confidence: 98%
“…This is probably because the exact nature of protein glycosylation in Plasmodium spp. has been contentious [2,3] and because glycopeptides were for a long time incorrectly thought to be T-independent antigens [4].Uncertainty surrounding protein glycosylation in Plasmodium parasites was driven in the past by an inability of common glycan-recognizing lectins to bind to parasite proteins and poor histological staining of parasites by periodic acid-Schiff methods. Indeed, it appeared that the installation of glycosylphosphatidylinositol anchors was the only type of glycosylation that Plasmodium parasites undertook [5].…”
mentioning
confidence: 99%
See 2 more Smart Citations